2007
DOI: 10.1287/orsc.1060.0231
|View full text |Cite
|
Sign up to set email alerts
|

Fairness from the Top: Perceived Procedural Justice and Collaborative Problem Solving in New Product Development

Abstract: T he literature on new product development has examined several important determinants of collaboration among project members. However, we are not aware of any study that links top management decisions with project members' collaborative behavior. To address this significant gap, this study examines how perceived procedural justice in top management decisions regarding new products is related to collaborative problem solving among new product development project members. Our results from 109 technology firms-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 83 publications
4
79
0
Order By: Relevance
“…The reason is that collaboration plays a prominent role in determining a group's creativity (Gilson and Shalley 2004, Leenders et al 2003, Li et al 2007, Sawyer 2007, particularly when the creative task requires interpersonal interaction and the integration of different idea components (Leenders et al 2007, Wood 1987. We define collaboration as the extent to which members of the group share their thoughts, consider each other's ideas and suggestions as valuable inputs into their own generative processes, and give meaning to each other's contributions (Baer et al 2010, Van Knippenberg et al 2004.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 99%
“…The reason is that collaboration plays a prominent role in determining a group's creativity (Gilson and Shalley 2004, Leenders et al 2003, Li et al 2007, Sawyer 2007, particularly when the creative task requires interpersonal interaction and the integration of different idea components (Leenders et al 2007, Wood 1987. We define collaboration as the extent to which members of the group share their thoughts, consider each other's ideas and suggestions as valuable inputs into their own generative processes, and give meaning to each other's contributions (Baer et al 2010, Van Knippenberg et al 2004.…”
Section: The Effects Of Intergroup Competition On Group Creativity: Smentioning
confidence: 99%
“…Tepper, Lockhart, and Hoobler (2001), found that procedural justice was positively related to organizational citizenship behavior (going above and beyond to help coworkers or the organization). Further, Li, Bingham, & Umphress (2007) found that procedural justice for top management decisions was positively related to collaborative problem solving for new product development. They found that when workers believed that the top management was likely to fairly make decisions, the workers were more likely to collaborate on new product development, which in turn increased new product performance.…”
Section: Nepotism and Organizational Justicementioning
confidence: 99%
“…Maximizing the perceived fairness of decisions has the potential to enhance innovation (Janssen 2000) and collaborative problem-solving (Li et al 2007). …”
Section: Introductionmentioning
confidence: 99%